Investigation of the Method of Authenticated Key Exchange - Ede, Cyril Chinonye (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
This thesis work investigates the method of authenticated key exchange, a key exchange protocol where communicating parties generate and exchange secret session keys for the purpose of authentication. We focused attention on the Efficient Two-Server Password-Only Authenticated Key Exchange by Xun Yi, San Ling, and Huaxiong Wang, the most recent authenticated key exchange protocol. The protocol uses two-server scenario to offer a symmetric solution for authenticated key exchange protocol in the password-only model. Before authentication process, the client chooses a password and computes password authenticator such that the password cannot be revealed from the authenticator to anyone, except the two servers conspired and sends to the two servers through a secure channel. The protocol generates shared session keys by each communicating party such that, in the result of their computations, parties arrive at a common session key. In our investigation, we discovered a problem with the protocol that will cause its failure and render it inefficient in general scenario. The problem is that the protocol does not take into account congruency of the exponents modulo Euler’s totient function, resulting in the parties arriving at different session keys at the end of computations, which we proved and illustrated by numerical counter-example. We provided a modification to the protocol by proposing that in choosing parameters whose inverses are involved in computations, care must be taken to ensure that their multiplicative inverses modulo Euler’s totient function exist. We provided a proof for the modification and a numerical example to illustrate the correctness of this modification and confirmed that the protocol works efficiently. With the proposed modification, it is certain the protocol will function without any failure. Keywords: Authenticated key exchange protocol, two-server architecture, password-only authentication, Diffie-Hellman, ElGamal encryption scheme

ÖZ : Bu çalışma, kimlik doğrulama amacıyla, iletişim içerisinde bulunan tarafların gizli oturum anahtarları oluşturup değiştirdiği bir kimlik anahtarı protokolü olan, kimliği doğrulanan anahtar değişimi yöntemini araştırmaktadır. Xun Yi, San Ling ve Huaxiong Wang tarafından geliştirilen ve en güncel kimliği doğrulanan anahtar değişimi protokolü olan Etkili İki-Sunuculu Yalnızca-Parolalı Kimliği Doğrulanan Anahtar Değişimi üzerine odaklanılmıştır. Yalnızca parola modelindeki kimliği doğrulanan anahtar değişimi protokolü için bir simetrik çözüm sunmak üzere protokol tarafından iki sunuculu bir örnek kullanılmaktadır. İstemci, kimlik doğrulama sürecinden önce bir parola seçer; ardından parola kimlik doğrulayıcısını, parolanın ilgili iki sunucu dışında gösterilmeyeceği şekilde hesaplar ve parolayı iki sunucuya güvenli bir kanal aracılığıyla gönderir. Protokol, her iletişim kuran taraf ile ortak oturum anahtarları oluşturur ve hesaplamaların bir sonucu olarak taraflar ortak bir anahtarda karar kılar. Araştırmamızda, protokol ile ilgili bir hataya rastlanmış ve genel olarak yetersiz bir şekilde işlenmesine neden olabilecek bir sorun keşfedilmiştir. Sorun, protokolün Euler totient fonksiyonu üs modulosunun eşleşikliğini değerlendirmemesi ve bunun bir sonucu olarak hesap sonlarında tarafların farklı oturum anahtarlarında bulunmalarıdır. Bu sorun sayısal örneklerle gösterilmiştir ve ispatlanmıştır. Hesaplamalarda tersleri bulunan parametreler seçerek protokole bir değişiklik sağlanmıştır. Bu durumda, çarpımsal tersler modulosu Euler toteint fonksiyonunun mevcut olduğu konusunda dikkatli olunmalıdır. Değişikliğin doğruluğunu gösteren bir kanıt ile sayısal bir örnek sunulmuştur ve protokolün etkili bir biçimde çalıştığı anlaşılmıştır. Önerilen değişiklik ile protokolün hata ile karşılaşmadan çalışacağı belirlenmiştir. Anahtar Sözcükler: Kimliği doğrulanan anahtar değişimi protokolü, iki sunuculu yapı, yalnızca parolalı kimlik doğrulama, Diffie-Hellman, ElGamal kriptolama düzeni.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2015. Supervisor: Assoc. Prof. Dr. Alexander Chefranov.
Keywords: Computer Engineering; Computer Networks - Security; Authenticated key exchange protocol; two-server architecture; password-only authentication; Diffie-Hellman; ElGamal encryption scheme